Extraction, Phytochemical Screening and Wound Healing Activity of Herbal Formulation of Saussurea lappa: Wound Healing and Anti-bacterial Activity of Saussurea lappa - Ahsan, Aitazaz; Miana, G. A.; Naureen, Humaira; RehmanA, Masood Ur; Anum, Kamil; Malik, Imran (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
The aim of present research work was to develop emulgel and In-situ gels of methanolic extract of Saussurea lappa with the purpose to determine their wound healing and anti-bacterial properties. Phyto-chemical analysis ofextract was also performed. Emulgel was prepared by using carbopol 940, Span 80, tween 80, polyethylene glycol (PEG 4000) and methyl paraben while in-situ gel was prepared by using polaxomer (P407) as thermo-sensitive andcarbopol (934P) as pH sensitive polymers. All formulations were maintained at pH 6-7 and stored at 4 ◦C. Lyophilizedextract was added in solution form to enhance the solubility as well as the stability. In-vitro release profile was performed by using Franz diffusion method and data was plotted in different pharmacokinetic models like first order,higuchi and hixon-crowell models. All formulations followed first order release mechanism. Hemolytic activity of extract was performed at concentration of 100μg/ml through heat induced hemolysis of erythrocyte membrane model system while anti-bacterial activity was determined by using agar well diffusion method. Acute toxicity assay of crude extract showed that 1000 mg/kg was safe dose with no toxic symptoms. Excision wounds were induced and wound healing potential of all formulations was determined. Results were compared and expressed as mean ± SEM, and data was analyzed by one way analysis of variance (ANOVA) with p<0.05.